Peningkatan pengetahuan kader dalam manejemen diri diabetes melitus melalui kelas edukasi kader - Zainuddin, Zainuddin; Sulistiani, Ita; Ahmad, Zul Fikar; Sartika, Sartika; Maryadi, Maryadi (Jurnal PADE: Pengabdian & Edukasi, 2024)
Diabetes mellitus is a metabolic disease characterized by an increase in blood sugar caused by disruption of the insulin hormone which has a function to maintain body homeostasis by lowering blood sugar levels. The expected goal after the implementation of this program is to increase the knowledge of cadres in compliance with diabetes mellitus management in cadres in Lemito District, Lomuli Village. This is intended for cadres with a total of 10 health cadres. The methods used in this activity include counseling and also providing Pre-tests and Post-tests. To find out the knowledge of cadres before and after being given counseling about Diabetes Mellitus. The results of the initial screening using a written pre-test question sheet showed that the cadres' knowledge of DM was around 6.1% where the results of the pre-test showed that the cadres did not know much about Diabetes Mellitus, and after the presentation of the material showed an increase in the cadres' knowledge of around 7.2% as evidenced by the written post-test question sheet.